2020
DOI: 10.25139/jsk.v4i2.2473
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the ‘home’: A literature review on Filipino migration and diaspora

Abstract: This article aimed to present a comprehensive literature review on Philippine migration and diaspora. Diaspora is not a new concept for Filipinos; they have been constantly connected to migration, one of the interconnected aspects of the global workforce. Diaspora and migration as common household terms can be traced back from the first overseas Filipino farmworkers in Hawaii in the middle of 1900s to the presently relocated skilled workers and domestic helpers in the Middle East countries and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For Filipinos, the idea of diaspora is nothing new; migration, one of the interwoven components of the global workforce, has always been associated with them (Aguilar, 2015;Labor, 2020;Lu, 2013;Misajon & Khoo, 2008). From the first offshore Filipino farmworkers in Hawaii in the middle of the 1900s to the skilled workers and domestic assistants currently relocated in Middle Eastern nations and other Asian nations, the terms' diaspora' and 'migration' have been popular household terms (Pacoma, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For Filipinos, the idea of diaspora is nothing new; migration, one of the interwoven components of the global workforce, has always been associated with them (Aguilar, 2015;Labor, 2020;Lu, 2013;Misajon & Khoo, 2008). From the first offshore Filipino farmworkers in Hawaii in the middle of the 1900s to the skilled workers and domestic assistants currently relocated in Middle Eastern nations and other Asian nations, the terms' diaspora' and 'migration' have been popular household terms (Pacoma, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many Migrant Women Worker takes this opportunity (Aguirre, 2014;Dwiantini, 1995;Quinsaat, 2016). Pacoma (2020) explains that migrant workers emphasise that poverty has forced them to work in other countries with the dream of providing for their families and improving their standard of living. Pacoma's statement is supported by Vargas et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, migrant workers represent migrants who provide many benefits to the country. Furthermore, Pedregosa (2019) found that Overseas Filipino Workers (OFWs) must make sacrifices and honourable deeds to advance the welfare of local and national communities (Pacoma, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations